2004
DOI: 10.1002/jcp.20189
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of claudin‐2 along the human intestine: Implication of GATA‐4 in the maintenance of claudin‐2 in differentiating cells

Abstract: Claudins, and particularly claudin-2, are important regulatory components of tight junction permeability. A better understanding of the involvement of claudin-2 in intestinal barrier functions requires the characterization of its distribution and regulation in the intestine. Interestingly, the claudin-2 gene promoter harbors a number of similarities to that of sucrase-isomaltase, a marker of enterocyte differentiation. We thus investigated the expression of claudin-2 in relation to the transcription factors CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
105
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(114 citation statements)
references
References 51 publications
7
105
1
1
Order By: Relevance
“…Another potential factor that may explain the observed conflicting reports is the different intestinal epithelial cell maturation and differentiation states. Caco2 cells express claudin-2 early following passaging and during proliferation; however, this tight junction protein is subsequently down-regulated during differentiation (54). Consistent with this, Prasad et al (36) observed decreased expression of claudin 2 and increased expression of claudin 3 and 4 over time and importantly demonstrated that these changes correlated with increased intestinal epithelial permeability.…”
Section: Discussionmentioning
confidence: 82%
“…Another potential factor that may explain the observed conflicting reports is the different intestinal epithelial cell maturation and differentiation states. Caco2 cells express claudin-2 early following passaging and during proliferation; however, this tight junction protein is subsequently down-regulated during differentiation (54). Consistent with this, Prasad et al (36) observed decreased expression of claudin 2 and increased expression of claudin 3 and 4 over time and importantly demonstrated that these changes correlated with increased intestinal epithelial permeability.…”
Section: Discussionmentioning
confidence: 82%
“…This protein is known to convert TJ from a tight to a leaky strand phenotype (20), and its expression is regulated by cingulin, another TJ cytoplasmic plaque protein that modulates proliferation in Madin-Darby canine kidney cells (27). The transcriptional regulation of CLDN2 by nuclear symplekin provides a potential explanation for the similarities of their expression pattern in human CRC, where claudin-2 also is overexpressed (23), and in healthy human and rodent colonic epithelia, where claudin-2 expression is restricted to the bottom section of the Lieberkühn crypts (28)(29)(30). In addition, because de novo experimental expression of claudin-2 restores the proliferation and anchorage-independent potential of cells with down-regulated symplekin, we conclude that claudin-2 is an essential mediator in the tumor-promoting role of symplekin.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was isolated from cultured cells and subjected to a DNase treatment according to the manufacturer's instructions (Totally RNA kit). Reverse transcriptions were carried out at 42°C for 1 h in the presence of 2 g RNA, 40 mU of polyoligo(dT) [12][13][14][15][16][17][18], and 40 U of Reverse Transcriptase (Roche Diagnostics). Semiquantitative PCR was performed in a total volume of 20 l in the presence of 1 l of RT reaction, 0.6 U of Taq DNA polymerase (New England Biolabs), 0.2 mM dNTPs, and 30 ng of each specific primer.…”
Section: Methodsmentioning
confidence: 99%
“…Cdx2, an intestinal epithelial specific transcription factor, regulates transcriptional activity of several intestinal epithelial-specific genes [for a review, see Guo et al (17)]. Other transcriptional regulators such as GATA-4 or hepatocyte nuclear factor-1␣ (HNF-1␣) cooperate with Cdx2 and regulate transcription of sucrase-isomaltase (SI) (6), lactase-phlorizin hydrolase (31,56), calbindin 3 (60), liver fatty acid binding protein gene (52), and claudin 2 (13,46). Restriction of apolipoprotein A-IV (ApoA-IV) expression to villus-differentiated enterocytes has been functionally linked to hepatocyte nuclear factor-4␣ (HNF-4␣) (49).…”
mentioning
confidence: 99%